Accessing nanoscopic polarization reversal processes in an organic ferroelectric thin film. Issue 46 (18th November 2021) - Mohapatra, Sambit; Beaurepaire, Eric; Weber, Wolfgang; Bowen, Martin; Boukari, Samy; Da Costa, Victor
Abstract : Nanoscopic switching current spectroscopy and polarization hysteresis loop, showing an enduring room temperature polarization, without leakage current, upon polarization reversal in vacuum sublimed thin films of croconic acid on cobalt surface. Abstract : Towards eliminating toxic substances from electronic devices, Croconic Acid (CA) has great potential as a sublimable organic ferroelectric material. While studies on CA thin films are just beginning to emerge, its capability to be integrated in nanodevices remains unexplored. We demonstrate at the laterally nanoscopic scale robust ferroelectric switching of a stable enduring polarization at room temperature in CA thin films, without leakage. The challenging ferroelectric characterization at the nanoscale is performed using a unique combination of piezoresponse force microscopy, polarization switching current spectroscopy and concurrent strain response. This helps rationalize the otherwise asymmetric polarization–voltage hysteresis due to background noise limited undetectable switching currents, which are statistically averaged in macrojunctions but become prevalent at the nanoscale. Apart from successfully estimating the nanoscopic polarization in CA thin films, we show that CA is a promising lead-free organic ferroelectric towards nanoscale device integration. Our results, being valid irrespective of the ferroelectrics' nature; organic or inorganic, pave the way for fundamental understandings and technological applications of nanoscopic polarization reversal mechanisms.